The Employers’ Perceptions and Satisfaction Concerning the Saudization of Accounting Jobs in the Hotel Sector: A Field Study in Makkah Al-Mukarramah - Baqader, Saleh Mohammed Saleh (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aimed to identify the employers’ perceptions and satisfaction regarding the Saudization of accounting jobs in the hotel sector. Examine the level of Saudization in the Hotel sector and challenges facing Saudi accountants to occupy accounting jobs in the hotel sector. The researcher employed an interview approach to collect the data to achieve the study objectives. Interviews were conducted with 17 hotel executives’ managers in Makkah, and interview data were analyzed manually. The results indicated that the hotel sector is satisfied with Saudi accountants’ performance and quality of work. In addition, the study showed that the percentage of Saudization of accounting jobs in the hotel sector exceeds 30% and reaches 70% in the hotel accounting professions. The results of the research found that the percentage of Saudi male employees in accounting professions is higher than Saudi female employees. The results showed that the English language is the primary difficulty Saudi accountants face in joining accounting jobs in the hotel sector. In addition, some of Saudi accountants in the hotel sector do not continue their work in hotels for long periods due to leaving work in the hotel once they obtain a job offer. Among the most important recommendations of the study, hotels should encourage Saudi accountants to work in the accounting profession, provide an attractive work environment, provide training opportunities for Saudi accountants, and motivate employees with annual raises and bonuses. Educational intuitions should set development programs to train and qualify Saudi accountants to work in the hotel sector.